WORKING CAPITAL MANAGEMENT STRATEGIES OF NIGERIAN MANUFACTURING INDUSTRIES AND FIRMS VALUE - Chris-Ejiogu , Uzoamaka Gloria; Edomobi, Nonye; Ozurumba , Benedict Anayochukwu; Obieche, Nkechi Precious (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This research explores the capital management strategies employed by Nigerian manufacturing industries and their impact on firm value, as measured by Earnings per Share (EPS). Employing an ex post facto research design, the study focuses on a population of 25 industrial goods industries, selecting a sample of 9 quoted manufacturing firms. The independent variables encompass various working capital management strategies, including accounts receivable management, accounts payable management, inventory management, cash conversion cycle, cash conversion efficiency, current assets to total assets ratio, and current liabilities to total assets ratio. The dependent variable is firm value, proxied by EPS. Results reveal both short-term and long-term effects of working capital management on EPS. The long-run model demonstrates significant negative relationships between accounts receivable management (ARM) and EPS, suggesting that efficient management of accounts receivables has a significant impact on financial performance. Conversely, accounts payable management (APM) exhibits a positive but non-significant effect. Inventory management (INVM) and cash conversion cycle (CCC) are positively related to EPS, with CCC and cash conversion efficiency (CCE) having significant effects. In the short run, the error correction model (ECM) indicates a negative and significant impact of deviations in accounts receivable management and cash conversion cycle on EPS. The study recommends among others that organizations focus on enhancing short-term corrective measures, such as agile and responsive strategies in accounts receivables, to ensure immediate and efficient impacts on financial performance.